(untitled) (Revista LIDER, 2017)
The developing countries have implemented fiscal policy strategies for growth and development through investment and consumption, particularly with tax incentives destined to improving social welfare. The challenges to the sustainability of the system will generate costs for the state and should be evaluated with the aim of achieving positive, both economic and social outcomes, so that the confidence of businesses and taxpayers are not fractured, promoting tax equity. This paper provides an outline of how fiscal policy works in achieving the development of a region, emphasizing the case of the implementation of Special Economic Zones (SEZ) in Mexico, following a qualitative descriptive methodology.